2015
DOI: 10.1007/s00436-015-4333-2
|View full text |Cite
|
Sign up to set email alerts
|

On the systematic position of Collyricloides massanae Vaucher, 1969 (Platyhelminthes: Digenea) with notes on distribution of this trematode species

Abstract: The systematic position of the Collyricloides massanae, a rare cyst-dwelling parasite, located on intestinal wall of European birds and rodents, have always been controversial. Based on newly obtained sequences of the 28 sDNA of C. massanae from avian and rodent host from Central Europe, and on the previously published sequences of several genera and families among Microphalloidea, we evaluate its taxonomic position and the phylogenetic relationships within the genera Collyriclum Kossack, 1911 and Collyricloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Tkach et al, 2003 in a study on molecular phylogeny and morphological data of the Microphalloidea Ward, 1901 synonymized Candidotrema Dollfus, 1951 with Pleurogenes Looss, 1896. Our study has revealed the phylogenetic similarity of P. cyanophlycti and P. euphlycti and allocated their correct systematic position that they be longs to the family Pleurogenidae within the superfamily Microphalloidea, that corresponds to the trees generated in other studies (Kanarek et al, 2014(Kanarek et al, , 2015(Kanarek et al, , 2017Bella et al, 2018;Tkach et al, 2019). Though, for molecular study of Pleurogenoides we have only one representative spe cies, P. medians and more data are required for a more congruent phylogeny.…”
Section: Resultssupporting
confidence: 69%
“…Tkach et al, 2003 in a study on molecular phylogeny and morphological data of the Microphalloidea Ward, 1901 synonymized Candidotrema Dollfus, 1951 with Pleurogenes Looss, 1896. Our study has revealed the phylogenetic similarity of P. cyanophlycti and P. euphlycti and allocated their correct systematic position that they be longs to the family Pleurogenidae within the superfamily Microphalloidea, that corresponds to the trees generated in other studies (Kanarek et al, 2014(Kanarek et al, , 2015(Kanarek et al, , 2017Bella et al, 2018;Tkach et al, 2019). Though, for molecular study of Pleurogenoides we have only one representative spe cies, P. medians and more data are required for a more congruent phylogeny.…”
Section: Resultssupporting
confidence: 69%
“…In total, 54 sequences were used for the alignment (supplementary table S1, after Tkach et al ., 2000, 2001, 2003; Olson et al ., 2003; Galaktionov et al ., 2012; Lord et al ., 2012; Greiman et al ., 2013; Heneberg & Literák, 2013; Kanarek et al ., 2014, 2015, 2017; Kudlai et al ., 2015a, b, 2016). The sequences were aligned using the Muscle algorithm (Edgar, 2004) as implemented in SeaView 4.0 (Gouy et al ., 2010) followed by a manual alignment verification.…”
Section: Methodsmentioning
confidence: 99%
“…The revision of the Pleurogenidae is far from completion, with genera being constantly added to or removed from this family (Kanarek et al, 2014(Kanarek et al, , 2015(Kanarek et al, , 2017Tkach et al, 2019Tkach et al, , 2023. Therefore, it would be inappropriate to suggest an amended diagnosis of the Pleurogenidae at this stage.…”
Section: Discussionmentioning
confidence: 99%
“…The taxonomy of the Pleurogenidae has recently been clarified with the use of molecular methods. In particular, the pleurogenid concept has been confirmed for Collyricloides Vaucher, 1969, Cortrema Tang, 1951, Gyrabascus Macy, 1935, Leyogonimus Ginetsinskaya, 1948, Macyella Neiland, 1951, Parabascus Looss, 1907and Urotrema Braun, 1900, which were previously recognized as members of six distinct families (Tkach et al, 2002(Tkach et al, , 2003(Tkach et al, , 2019Blair, Barton, 2008a, b;Lotz, Font, 2008a-d;Kanarek et al, 2014Kanarek et al, , 2015Kanarek et al, , 2017Sokolov et al, 2020;Kirillova et al, 2022). Moreover, Collyriclum Kossack, 1911 (type genus of Collyriclidae) appears in the recent phylogenetic reconstructions as a member of the Pleurogenidae + Collyriclidae clade, in which the pleurogenids form a paraphyletic assemblage (Shchenkov et al, 2020(Shchenkov et al, , 2022Sokolov et al, 2020;Kirillova et al, 2022).…”
Section: Introductionmentioning
confidence: 89%